2019
DOI: 10.1108/mrr-05-2019-0221
|View full text |Cite
|
Sign up to set email alerts
|

Creditworthiness and access to finance: a study of SMEs in the Malaysian manufacturing industry

Abstract: Purpose The purpose of this study is to empirically assess the relationship between the dimensions of creditworthiness and access to finance of small and medium-sized enterprises (SMEs) in Malaysia, with creditworthiness as the mediating variable. The lack of empirical research on the relationship between creditworthiness and access to finance forms the motivation of this study. Design/methodology/approach Questionnaires covering various characteristics of the firms, their access to finance and creditworthin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
3
34
0
1
Order By: Relevance
“…We found that firms' financial accessibility was crucial to their intellectual capital. According to our research, which obtained the same result as that of Wasiuzzaman et al (2020), concluded that the use of financial goods and services was good for the development of micro-enterprises. Additionally, financial access encourages MSMEs to expand because it alleviates unexpected economic shocks and market fluctuations in their operations (Bakhadirov et al, 2020).…”
Section: Discussion Of the Findingssupporting
confidence: 65%
See 2 more Smart Citations
“…We found that firms' financial accessibility was crucial to their intellectual capital. According to our research, which obtained the same result as that of Wasiuzzaman et al (2020), concluded that the use of financial goods and services was good for the development of micro-enterprises. Additionally, financial access encourages MSMEs to expand because it alleviates unexpected economic shocks and market fluctuations in their operations (Bakhadirov et al, 2020).…”
Section: Discussion Of the Findingssupporting
confidence: 65%
“…Leveraging increased financial market competition offers the opportunity for people to put their risk management skills and expertise to use. Financial access has also been shown to be helpful for entrepreneurs when dealing with banks and providing micro businesses with the ability to navigate the challenges presented by changing financial markets, leading to growth (Wasiuzzaman, 2019;Wasiuzzaman et al, 2020). Having financial access leads to both direct and indirect companies.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Banks, to meet market requirements, have to adopt standard processes and procedures of corporate lending to the real needs of SMEs taking a cue from the special features of such businesses (Cusmano & Koreen, 2015). In the vast majority of cases, lenders face the problem of the preliminary assessment of the borrower's creditworthiness, based on the analysis of the borrower's projected financial reports (Wasiuzzaman et al, 2019;Caner & Karan, 2012;Polishchuk et al, 2020;Khovrak & Petchenko, 2015;Dubyna et al, 2021) and try to find cash-flows eligible for loan servicing. One of the problems is that in some cases, an SME, as a potential borrower, does not have the indiscrete series of positive cash flows dedicated to loan servicing.…”
Section: Introductionmentioning
confidence: 99%
“…Mismatched funding could affect SMEs' business performance as a study conducted by Mustafa, Sam and Ismail (2019) revealed a positive relationship between facility structure and SMEs' performance. There are many reasons why SMEs are facing difficulties in securing fundings, one of which is lack of collateral, as suggested by Wasiuzzaman, Nurdin, Abdullah and Vinayan (2020), Haron, Said, Jayaraman and Ismail (2013) and Zairani and Zaimah (2013).…”
Section: Introductionmentioning
confidence: 99%